Teaching Strategies for Enhancing Vocabulary Mastery of Indonesian EFL Learners - Mulis (English Language Teaching Journal, 2025)
Vocabulary mastery is essential for effective communication in language learning, yet students often struggle with understanding and retaining new words. This study aimed to explore the strategies used by an English teacher to enhance vocabulary mastery in the Bilingual Class at MTsN 1 Gondanglegi Malang. A descriptive qualitative approach was employed, involving one English teacher and seventh-grade students as participants. Data were collected through classroom observations and Focus Group Interviews (FGI), with an iterative technique applied to ensure data richness. The analysis included familiarizing and organizing, coding and reducing, and interpreting and representing the data. Credibility and confirmability were maintained through triangulation of observation, FGI, and audit trails such as video and record documentation. The findings revealed four main teaching strategies: text-based teaching, dictionary use, memorization, and blended-skills instruction. The study also identified key challenges, including students’ limited understanding of vocabulary and their tendency to forget new words. Based on these findings, it is recommended that teachers integrate more interactive and innovative strategies to enhance vocabulary retention and engagement. The study provides practical implications for EFL teachers and contributes to the literature on effective vocabulary teaching strategies.